Back‐to‐back colon capsule endoscopy and optical colonoscopy in colorectal cancer screening individuals. (3rd June 2018) - Kobaek‐Larsen, M.; Kroijer, R.; Dyrvig, A.‐K.; Buijs, M. M.; Steele, R. J. C.; Qvist, N.; Baatrup, G.
Abstract: Aim: The aim was to determine the polyp detection rate and per‐patient sensitivity for polyps > 9 mm of colon capsule endoscopy (CCE) compared with colonoscopy as well as the diagnostic accuracy of CCE. Method: Individuals who had a positive immunochemical faecal occult blood test during screening had investigator blinded CCE and colonoscopy. Participants underwent repeat endoscopy if significant lesions detected by CCE were considered to have been missed by colonoscopy. Results: There were 253 participants. The polyp detection rate was significantly higher in CCE compared with colonoscopy ( P = 0.02). The per‐patient sensitivity for > 9 mm polyps for CCE and colonoscopy was 87% (95% CI: 83–91%) and 88% (95% CI: 84–92%) respectively. In participants with complete CCE and colonoscopy examinations ( N = 126), per‐patient sensitivity of > 9 mm polyps in CCE (97%; 95% CI: 94–100%) was superior to colonoscopy (89%; 95% CI: 84–94%). A complete capsule endoscopy examination ( N = 134) could detect patients with intermediate or greater risk (according to the European guidelines) with an accuracy, sensitivity, specificity and positivity rate of 79%, 93%, 69% and 58% respectively, using a cut‐off of at least one polyp > 10 mm or more than two polyps. Conclusion: CCE is superior to colonoscopy in polyp detection rate and per‐patient sensitivity to > 9 mm polyps, but only in complete CCE examinations. The rate of incomplete CCE examinations must be improved.